A Simple Predictive Enhancer Syntax for Hindbrain Patterning Is Conserved in Vertebrate Genomes. - Joseph Grice; Boris Noyvert; Laura Doglio; Greg Elgar (PLoS ONE)
Background Determining the function of regulatory elements is fundamental for our understanding of development, disease and evolution. However, the sequence features that mediate these functions are often unclear and the prediction of tissue-specific expression patterns from sequence alone is non-trivial. Previous functional studies have demonstrated a link between PBX-HOX and MEIS/PREP binding interactions and hindbrain enhancer activity, but the defining grammar of these sites, if any exists, has remained elusive. Results Here, we identify a shared sequence signature (syntax) within a heterogeneous set of conserved vertebrate hindbrain enhancers composed of spatially co-occurring PBX-HOX and MEIS/PREP transcription factor binding motifs. We use this syntax to accurately predict hindbrain enhancers in 89% of cases (67/75 predicted elements) from a set of conserved non-coding elements (CNEs). Furthermore, mutagenesis of the sites abolishes activity or generates ectopic expression, demonstrating their requirement for segmentally restricted enhancer activity in the hindbrain. We refine and use our syntax to predict over 3,000 hindbrain enhancers across the human genome. These sequences tend to be located near developmental transcription factors and are enriched in known hindbrain activating elements, demonstrating the predictive power of this simple model. Conclusion Our findings support the theory that hundreds of CNEs, and perhaps thousands of regions across the human genome, function to coordinate gene expression in the developing hindbrain. We speculate that deeply conserved sequences of this kind contributed to the co-option of new genes into the hindbrain gene regulatory network during early vertebrate evolution by linking patterns of hox expression to downstream genes involved in segmentation and patterning, and evolutionarily newer instances may have continued to contribute to lineage-specific elaboration of the hindbrain.